Radiological nodule behavior: A critical parameter in the surgical management of pediatric pulmonary metastases - Divarcı, Emre; Arslan, Serkan; Dökümcü, Zafer; Kantar, Mehmet; Demirağ, Bengü; Öniz, Haldun; Ertan, Yeşim; Alper, Hüdaver; Erdener, Ata; Özcan, Coşkun (The Turkish Journal of Pediatrics, 2018)
Radiological nodule behavior (RNB) means the course of nodule appearance on consecutive CT scans. In this study, we aimed to discuss the effects of RNB on prognosis of patients with pulmonary metastasis. Retrospective analysis of patients who underwent pulmonary metastasectomy (PM) between 2005-2015 was performed. RNBs were grouped as stable, enlarging or new rising nodules. The effects of RNBs were analyzed on recurrence, 1- and 3-year event free survival (EFS) and mortality. Twenty-seven patients (18 male) underwent PM with a median age of 15 years (3-18 years). The diagnoses were listed as osteosarcoma (13), Wilms` tumor (7), Ewing`s sarcoma (3), synovial sarcoma (2), rabdomyosarcoma (1) and mixed germ cell tumor of testis (1). RNBs were new rising in 15 patients (55%), enlarging in seven patients (26%) and stable in five patients (19%). Vital tumor metastasis was detected in all of the patients with enlarging nodules (100%); in 10 of the 15 patients with new rising nodules (66%) and none of the patients with stable nodules. None of the patients with stable nodules developed recurrence or died after PM (p˂0.05). In patients with enlarging nodules, metastases recurred and they died in the postoperative period. These findings were similar in different types of tumors. RNB could be used as a critical parameter in deciding surgical management strategies of pulmonary metastases. Stabile nodules should be observed by close follow-up with serial CT scans without surgery. All of the suspected new rising nodules should undergo surgical sampling to avoid unnecessary chemotherapy. Nodule progression under chemotherapy is a poor prognostic criteria for overall survival.
Keywords: children; osteosarcoma; pulmonary metastasectomy; pulmonary metastasis; pulmonary nodule